Occurrence of Oligochaeta species (Annelida: Clitellata) in Rivers in the State of São Paulo (Brazil) (Revista Brasileira Multidisciplinar, 2022)
The knowledge about the diversity and fauna distribution in tropical freshwater ecosystems is of extreme ecological importance, however studies on this theme still scarce. Organisms belonging to the Oligochaeta Class are considered important bioindicators for environmental quality analysis, but detailed knowledge about these organisms is still insufficient. This study aims to investigate the occurrence of oligochaeta species in eight rivers of the State of São Paulo (Brazil), to expand the species catalogue and identify the its relationship with the trophic state of sampled environments. The samples were collected by the Environmental Company of the State of São Paulo (CETESB) from 2014 to 2016 and include areas with different land uses, ranging from conservation, agricultural and industrial. We used species richness estimator (Bootstrap) and accumulation curves of randomized species (collector curve), in order to evaluate the efficiency of samples collected. Rivers were classified according to the trophic state, ranging from oligotrophic to hypereutrophic. As a result, we identified a total of 7,398 oligochaetes distributed in 25 taxa, which belong to the families: Alluroididae, Naididae and Opistocystidae. The most frequent species registered in this research, present in seven of the eight sampled rivers was Bothrioneurum sp., followed by Pristina synclites registered in six of the eight sampled rivers.
Keywords: Classe Oligochaeta; Corpos hídricos; Oligoquetos aquáticos; Organismos bioindicadores; Registro de espécies